In vitro cellular uptake of evodiamine and rutaecarpine using a microemulsion - Zhang YT (Dove Medical Press, 2012)
Yong-Tai Zhang, Zhe-Bin Huang, Su-Juan Zhang, Ji-Hui Zhao, Zhi Wang, Ying Liu, Nian-Ping FengDepartment of Pharmaceutics, Shanghai University of Traditional Chinese Medicine, Shanghai, The People's Republic of ChinaObjective: To investigate the cellular uptake of evodiamine and rutaecarpine in a microemulsion in comparison with aqueous suspensions and tinctures.Materials and methods: A microemulsion was prepared using the dropwise addition method. Mouse skin fibroblasts were cultured in vitro to investigate the optimal conditions for evodiamine and rutaecarpine uptake with different drug concentrations and administration times. Under optimal conditions, the cellular uptake of microemulsified drugs was assayed and compared to tinctures and aqueous suspensions. Rhodamine B labeling and laser scanning confocal microscopy (LSCM) were used to explore the distribution of fluorochrome transferred with the microemulsion in fibroblasts. Cellular morphology was also investigated, using optical microscopy to evaluate microemulsion-induced cellular toxicity.Results: The maximum cellular drug uptake amounts were obtained with a 20% concentration (v/v) of microemulsion and an 8 hour administration time. Drug uptake by mouse skin fibroblasts was lowest when the drugs were loaded in microemulsion. After incubation with rhodamine B-labeled microemulsion for 8 hours, the highest fluorescence intensity was achieved, and the fluorochrome was primarily distributed in the cytochylema. No obvious cellular morphologic changes were observed with the administration of either the microemulsion or the aqueous suspension; for the tincture group, however, massive cellular necrocytosis was observed.Conclusion: The lower cellular uptake with microemulsion may be due to the fact that most of the drug loaded in the microemulsion vehicle was transported via the intercellular space, while a small quantity of free drug (released from the vehicle) was ingested through transmembrane transport. Mouse skin fibroblasts rarely endocytosed evodiamine and rutaecarpine with a microemulsion as the vehicle. The microemulsion had no obvious effect on cellular morphology, suggesting there is little or no cellular toxicity associated with the administration of microemulsion on mouse skin fibroblasts.Keywords: mouse skin fibroblasts, evodiamine, rutaecarpine, microemulsion, cellular uptake, in vitro